PENGARUH PENGGUNAAN ENDOCARP SAWIT UNTUK STABILISASI TANAH LUNAK PEATLAND - Misnawati; Marlia Adriana; Norminawati Dewi; Suhaimi (P3M Politeknik Negeri Tanah Laut, 2023)
During this use Endocarp mostly produced by the oil palm plantation industry. Research is done by mixing Endocarp oil palm that has been sun-dried with maximum dry conditions along with soft clay soil with a content of Endocarp 4%, 6%, and 8%. The sample used in this study is a samples undisturbed , and samples disturbed prepared in the laboratory by mixing clay and Endocarp with a variation of the mixture used is 4%, 6%, and 8% from one bag of clay weighing 2 kg. There is a mix Endocarp the following results were obtained: equal to 1.37 gram/cm3 with a water content of 24.72% (original soil). The CBR value of the mixture Endocarp this study 4%, 6%, 8% obtained the result that the CBR value is mixed Endocarp 4% has the greatest CBR value, which is equal to 7.99% (Unsocked) and 6.69% (socked). The UCT value of the soil will increase in the presence of a mixture Endocarp until mixed Endocarp added by 4% and the UCT value will decrease after the mixture Endocarp above 8% fiber content, maximum UCT value is produced in the mixture Endocarp 4% with a qu value of 0.9295 kg/cm2. The value of the soil shear resistance (su) on the test Vane Shear Test continued to improvement in the mixture Endocarp as much as 4% worth 92 kPa (25 blow condition).